A strategic analysis of the local banking industry - Ng, Kair Yeow (2014)
Over the past four decades, the local banking industry had grown from strength to strength. Started off as financial institutions mainly providing trade financing to the local merchants and entrepreneurs, the local commercial banks had developed into internationally reputed institutions engaging in wide range of local and offshore financial activities.